THE EFFECT OF TASTE AND IMAGE OF TOURISM DESTINATIONS ON CUSTOMER SATISFACTION AND LOYALTY (Study at Warung Bu Sari, the Tourist Destination of Gubug Serut) - Demi Kartika; Bambang Sutedjo (Jurnal Ekonomi, 2023)
The purpose of this study was to analyze the effect of the taste and image of a tourist destination on customer satisfaction and loyalty at Warung Bu Sari in Semarang City . The sample in this study were 112 customers of Warung Bu Sari in Semarang City . Determination of the sample in this study using purposive sampling . The analysis tool used is multiple linear regression analysis and Sobel Test. The results of the analysis can be concluded that: taste has a positive effect on customer satisfaction . Destination image has a positive effect on customer satisfaction. Taste has a positive effect on customer loyalty. Destination image has a positive effect on customer loyalty. Customer satisfaction has a positive effect on customer loyalty.